Chitotriosidase attenuates microglia‐associated inflammation via HDAC3/NF‐κB pathway in D‐galactose and aluminum‐induced rat model with cognitive impairments: Molecular and cell biology/neurodegeneration and neuroprotection. (7th December 2020) - Yu, Xingyan; Yu, Weihua; Wu, Lihua; Yang, Wenkai; Lü, Yang
Abstract: Background: Chitotriosidase (CHIT1, chitinase 1) is elevated in the cerebrospinal fluid and peripheral blood of Alzheimer's disease (AD) patients. Our previous study has shown that CHIT1 provides potential protection through microglial polarization and reduction of β‐amyloid (Aβ) oligomers on rats models of AD. Histone deacetylase 3 (HDAC3) plays an important regulatory role in the expression and regulation of proteins associated with AD pathophysiology. In addition, nuclear factor‐kappa B (NF‐κB) signaling pathway activation in neurons is involved in the development and progression of AD. NF‐κB activation is regulated by HDAC3 deacetylation. In this study, we investigated the role of CHIT1 in HDAC3/NF‐κB signaling in D‐galactose and aluminum‐induced rat model with cognitive impairments. Method: Rats in each group were euthanized and transcardial perfusion was performed with 0.9% saline. Brain tissues (cortex and hippocampus) from these rats were quickly removed. The prepared samples were used for western blotting (WB), and real‐time polymerase chain reaction (RT‐PCR). For paraffin sections, rats were anesthetized and perfused with 4% paraformaldehyde following normal saline infusion. Once the limbs became stiff, the brains were removed for dehydration, embedding and sectioning. Result: We found that the protein and mRNA levels of HDAC3 and NF‐κB were reduced after CHIT1 treatment, and the expression level of IκBα increased after CHIT1 treatment. Anti‐inflammatory factors (Arg‐1, IL‐10, and CD206) were increased while pro‐inflammatory factors (TNF‐a, IL‐1β, and iNOS) were decreased in D‐galactose/aluminum‐induced AD rats with CHIT1 treatment. Conclusion: These results indicate that CHIT1 can regulate microglial polarization via HDAC3/NF‐κB p65 pathway in D‐galactose and aluminum‐induced rat model with cognitive impairments.